MISIOLOGI SEBAGAI ALAT TRANSFORMASI SOSIAL DALAM PENDIDIKAN AGAMA KRISTEN - Anton Ramba; Asra Leoni Tambing; Kristina; Yosi Rosita Karmila; Febidriati Rara' (ADIBA : JOURNAL OF EDUCATION, 2024)
This study, titled "Missiology as a Tool for Social Transformation in Christian Religious Education," aims to explore how the principles of missiology can be applied within the context of Christian religious education to promote positive social change. Using a qualitative research method with a literature review approach, the study collects and analyzes various written sources, including books, journal articles, and research reports relevant to missiology and Christian education. The main findings indicate that integrating missiology into the Christian education curriculum can enhance students' awareness and engagement with social issues and facilitate the development of missionary character. The study also identifies challenges and obstacles in applying missiology, such as resistance to change and resource limitations. Recommendations are provided to improve the implementation of missiology in Christian education, emphasizing the importance of institutional support and the use of information technology. This research contributes to understanding how Christian education can serve as a tool for social transformation through a missiological approach.